The Headmaster’s Strategies In Implementing Management Based On Schools In Smp Muhammadiyah Solokuro Lamongan - Arifin, Zainal (TADARUS, 2019)
AbstractThis study aims to find out and explore how does the headmaster implementit? what is the obstacle facing him? what strategy is done? This researchuses four approaches that are pedagogies, sociological, juridical andpsychological. The sources of the data are primary and secondary. Theinstruments are interviews, observation guides, check list observation, anddocumentation. The research techniques are data reduction techniques, datapresentation, and conclusions. From the results of the research of schoolbasedmanagementinSMPMuhammadiyahSolokuroLamongan,it can beconcluded: The headmaster has implemented school-based management butthe implementation has not fully implement school-based management. Theheadmaster as a leader using School Based Management still needsimprovement and improvement of teacher quality and good cooperationwith school partners. Constraints faced a) Lack of educational facilities andinfrastructure b) lack of teacher competency c) lack of parental support oflearning process, d) lack of intensive and maximal socialization, e) lack ofmaster of technology. Strategies undertaken in implementing school-basedmanagement ie a) doing relationship with relevant agencies to provide thefacilities and the infrastructure b) improving teacher competence byinvolving teachers in trainings c) doing relationship with parents to improvethe quality of education. The implications of this research is expected for theheadmasters and teachers to always perform their duties and functionsrespectively each other. To the teachers of SMP MuhammadiyahSolokuroLamongan, to always strive to improve the professionalism ofwork for the quality of school education in particular and in general can bebetter. To the relevant agencies would pay attention to the development ofeach school.Keywords: Strategy,Leadership, Management